Low-cost method for quantification of salicylic acid loaded in lipid nanoparticles containing copaiba oil (Research, Society and Development, 2022)
The demand for analytical methods for drug quantification is an obstacle in the research and development of new products, due to the need to use simpler techniques for the identification and quantification of the actives. Although it is a very sensitive and selective technique for these determinations, high performance liquid chromatography (HPLC) requires expensive instrumentation and well-trained analysts, while spectrophotometry is fast, low-cost and hardly requires sample pre-treatment. Thus, this study aimed to develop a quantification method by UV-visible spectrophotometry for salicylic acid (SA) encapsulated in nanostructured lipid carriers (NLC) containing copaiba oil. The method was validated according to national and international criteria (ANVISA, ICH and FDA). The diluent was a mixture of absolute ethanol and phosphoric acid (99:1) and detection was performed at 310 nm. The interference of the matrix in relation to NLC-SA was minimal (0.37%), demonstrating the selectivity. Linearity was obtained in the range of 5.0 30.0 μg/mL (r = 0.99948) and the method proved to be accurate, with high recovery of SA in the presence of the other components (over 96% recovery), with precision at two levels: intra- and inter-days (DPR < 5%). Detection and quantification limits were 0.51 e 1.70 μg/mL, respectively. Finally, according to the Youden test criteria, the method was robust in the face of the proposed variations, obtaining effect values lower than the critical value (0.07). Therefore, the developed method is accessible, effective and valid for the quantification of SA in complex matrix lipid nanoparticles.